Getting Engaged in America - Aldrovandi, Makeli (BELT - Brazilian English Language Teaching Journal, 2014)
Introduction: The National Curricular Parameters of 2000 point out a new path for the teaching of foreign languages in Brazilian school. They determine that the language must be taught in such a way that it enables students to actually communicate by using the language. They also suggest that the teaching of a foreign language should allow students to learn about foreign cultures as well. The National Curricular Parameters (2000:25) state that, “the Foreign Languages take on the condition of being an indissoluble part of the set of essential knowledge that allow the student to approach several cultures and, consequently, promote his integration in a globalized world”. Furthermore, the National Curricular Parameters assert that grammar must be taught in context and not isolated as it used to be. Thus, this lesson plan has as its theoretical support those two ideas of the National Curricular Parameters: enabling students to learn about foreign cultures and teaching, or in the case of this plan in specific, reviewing a grammar topic in a real context of use.